Plasmon resonance in photoabsorption of colloidal highly doped ZnO nanocrystals - Ipatov, Andrey N. (2018)
A new type of dipole plasmon excitations in colloidal highly doped ZnO nanocrystals has been studied by means of many-body quantum mechanical approach. We demonstrate that in photodoped ZnO nanocrystals, the conduction band electrons are localized close to the surface and the plasmon oscillations are induced by their angular motion. The transition of this plasmon mode from classical to quantum regime is defined by the nanocrystal size. The size dependence of the resonance frequency which results from quantum effects is in remarkable agreement with experimental observations.